Severe pneumonia due to concurrent Legionella pneumophila and Acinetobacter baumannii infections: a case report - Xiaoming Yang; Zhongda Liu; Xiaojing Liu; Quan Li; Hui Huang; Yibo Wei; Tao Sun (BMC Pulmonary Medicine)
Abstract Background Legionella pneumophila is an uncommon pathogen causing community-acquired atypical pneumonia. Acinetobacter baumannii is a major pathogen responsible for hospital-acquired pneumonia, but it rarely causes serious infections in a community setting. Without prompt and appropriate treatments, infection from either of these two pathogens can cause a high mortality rate. Concurrent infection from both L. pneumophila and A. baumannii can cause serious outcomes, but it has rarely been reported previously. Case presentation A 45-year-old male presented to our hospital with a productive cough and fever after staying in a local hotel. His chest computed tomography (CT) scan showed bilateral lower-lobe infiltration and left pleural effusion. Empirical antibiotics, including piperacillin-tazobactam, levofloxacin, meropenem, and doxycycline, were administered to him to treat community-acquired pneumonia. However, his condition deteriorated very rapidly, and he required endotracheal intubation and mechanical ventilation for respiratory support. Finally, metagenomic next-generation sequencing (mNGS) of his bronchoalveolar lavage fluid identified L. pneumophila and A. baumannii. The sputum culture demonstrated multidrug-resistant A. baumannii. He was diagnosed with pneumonia by concurrent infections from both L. pneumophila and A. baumannii. After careful consideration of the antibiotic susceptibility results and the antibacterial mechanism of each antibiotic, we switched the antibiotics to omadacycline and cefoperazone/sulbactam. His clinical symptoms gradually subsided. The repeat chest CT image showed no infiltration or pleural effusion. Conclusions Community-acquired pneumonia can be caused by concurrent infections of both L. pneumophila and A. baumannii. Close clinical monitoring, early pathogen detection and antibiotic susceptability tests, and appropriate antibiotic regimen adjustments should be applied to these patients who failed initial antibiotic treatments.